Design and Development of Soil Battery System for Sustainable Energy Storage - Suradi, Mohamad Shafiq Haikal; Mohamad , Khairul Anuar (Evolution in Electrical and Electronic Engineering, 2023)
Every day, the renewable energy and alternative power industries are growing, resulting in reduced global warming, enhanced public health, abundant electricity, and affordable energy prices. One of alternative power source is the soil-battery, which can be utilized without relying on external power for charging. It naturally charges itself when in contact with water. This work aims to demonstrate the process of electricity generation from soil and its application in operating small-scale devices. Initially, different soil samples, influential reactors, and electrodes were analyzed to determine the complete potential difference and electron flow. The soil battery represents a recent development in clean energy. The soil battery system was developed using components setup such as copper spikes, galvanized nails and copper wire as cathodes, anodes and conductors, respectively for the generation of electricity from the moist soil. By four fundamental materials such as copper cathodes, zinc anodes, copper conductors and moist soil, a battery system can generate enough power to operate low-consumption loads offering a sustainable solution for generating electricity. For example, the 100% of moisture level of clay soil managed to generate maximum voltage and power which are around 5.7 V and 0.057µ W, respectively. Besides, the prototype of soil-battery system can power-up loads such as an LED (0.033µ W) and a calculator (0.033µ W) without the need for conventional batteries.